Kedudukan Bukti Elektronik dalam Pembuktian Perkara Perdata Pasca Penerapan Peradilan Digital - Shifa Arifatunnisa; Sidi Ahyar Wiraguna (Media Hukum Indonesia (MHI), 2026)
The digital transformation of Indonesia’s judiciary marked by the implementation of the e-Court system and the enactment of the Electronic Information and Transactions Law (ITE Law) has created a new legal space for electronic evidence in civil litigation. This article examines the legal standing of electronic evidence following the adoption of digital justice mechanisms, focusing on its admissibility, probative value, and practical challenges in courtroom application. Employing a normative juridical approach, the study finds that electronic evidence such as instant messages, emails, and digital documents is legally recognized as valid proof, provided it satisfies the principles of authentication, data integrity, and substantive relevance to the dispute. Nevertheless, its integration into the civil procedural framework remains hampered by regulatory misalignment between the ITE Law and classical civil procedure rules (HIR/RBg), the absence of technical guidelines for verification, and limited judicial capacity in digital forensic assessment. These findings underscore the urgent need for normative harmonization and enhanced technological literacy among legal practitioners to ensure a fair, efficient, and digitally responsive justice system.